Benzoin thiosemicarbazone and benzoin 4-ethylthiosemicarbazone - Dincer, Muharrem; Ozdemir, Namik; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Int Union Crystallography, 2006)
[Abstract Not Available]
Keywords: X-ray crystallography; small organic molecules; structure comparison